The Current Status of Forest Residues and Disposal Machinery in Turkiye - Gülci, Sercan; Sariyildiz, Temel; Akay, Abdullah Emin (Forest Engineering and Technologies Platform, 2024)
The term "cutting residue" is a widely used term in Turkey, which refers to the leftover pieces of logs in the forest after cutting, except for the logs. As of yet, there is no specific expression and explanation for the term "slash" in Turkish forestry. Turkey carries out intensive forestry activities based on industrial wood production, primarily in mature stands and damaged after disasters such as fire or storm fall. Products that do not carry industrial woodiness in the stand, such as branches, roots, and tips that are not suitable for industrial production, are considered firewood and used for energy production or left in the stand. As a result, it is observed that the collected cutting residues from the fields that are sufficient in terms of benefit and cost is burned to generate electricity in electricity generation stations. Due to the demand for forest-based wood raw materials in recent years, some domestic companies have begun converting thick branches into industrial products such as paper and chipboard production. Additionally, some studies have been conducted to reduce transportation costs in bringing cutting residues to the economy, focusing on the storage and processing of forest cutting residues on the landing sites. In this regard, small-scale chipping machines have been produced by the domestic industry. Therefore, slash disposal and mechanization have a very limited place in Turkish forestry. Decision makers need to prepare action plans in this regard and provide support to joint research projects with academic units. © Copyright 2024 by Forest Engineering and Technologies Platform.
Keywords: Energy; Feasibility; Forest biomass; Logging residue; Production; Turkiye